2013
DOI: 10.1155/2013/147238
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Caffeine following a Single Administration of Coffee Enema versus Oral Coffee Consumption in Healthy Male Subjects

Abstract: The objective of this study was to determine the pharmacokinetics of caffeine after single administration of a coffee enema versus coffee consumed orally in healthy male subjects. The study design was an open-label, randomized two-phase crossover study. Eleven healthy subjects were randomly assigned either to receive 500 mL of coffee enema for 10 minutes or to consume 180 mL of ready-to-drink coffee beverage. After a washout period of at least 10 days, all the subjects were switched to receive the alternate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 30 publications
1
44
0
1
Order By: Relevance
“…Although caffeine rectal enema is an ancient medical procedure that is still currently being used today, it was documented that such enema have risk of proctocolitis, polymicrobial enteric septicemia, electrolyte imbalance and maybe even fatal [2225]. Like oral administration, caffeine enemas also results in absorption into systemic circulation in the rectum and colon [26]. Therefore, whether caffeine exerts its effect directly on the intestine, or via bloodstream circulation, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although caffeine rectal enema is an ancient medical procedure that is still currently being used today, it was documented that such enema have risk of proctocolitis, polymicrobial enteric septicemia, electrolyte imbalance and maybe even fatal [2225]. Like oral administration, caffeine enemas also results in absorption into systemic circulation in the rectum and colon [26]. Therefore, whether caffeine exerts its effect directly on the intestine, or via bloodstream circulation, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether caffeine exerts its effect directly on the intestine, or via bloodstream circulation, remains to be determined. It was shown in human subjects that caffeine enema has 3.5 folds lower plasma caffeine concentration as compared to orally administered, though half-life of the two groups was not statistically any different [26]. In this study, we chose to orally administer caffeine into DSS-induced colitic mice to test if this convenient mode of drug delivery can achieve the desired improvement in colitis condition.…”
Section: Discussionmentioning
confidence: 99%
“…We measured hemodynamic variables throughout the experiment and baPWV at 30 and 60 min after caffeinated or decaffeinated coffee intake in a supine position because a plasma caffeine concentration reaches to peak at 0.44 h after oral coffee intake (Teekachunhatean et al. ). Each experimental protocol (Coffee and Placebo) was performed at least 2 h after a light meal in order to reduce the effect of individual diet on cerebral and peripheral vasculature.…”
Section: Methodsmentioning
confidence: 99%
“…() demonstrated that the risk of ischemic stroke increased only immediately after drinking coffee (within 1 h) because a plasma caffeine concentration reaches peak at around 0.5 h after oral coffee intake (Teekachunhatean et al. ) and caffeine acutely activates the central nervous system. Thus, the effect of drinking coffee on the cardiovascular system may be time dependent, although the mechanism behind the increase in the risk of ischemic stroke immediately after drinking coffee is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that caffeine absorption from the gastrointestinal tract is rapid and complete with the bioavailability of 99 to 100% after oral administration [107110]. Treatment with caffeine decreased the total number of mammary tumors in diethylstilbestrol (DES)-treated ACI rats [111].…”
Section: Natural Products Against Er-positive Breast Cancermentioning
confidence: 99%